PROBLEMATIKA KONTRAK BAKU DALAM AKAD MUDHARABAH DI LEMBAGA PERBANKAN SYARIAH - Naâim, Muhlishotu Jannati (IAIN Tulungagung, 2017)
The development of financing in Islamic banks illustrates that this productenjoyed by many people. Financing is one option the community to cooperatewith the banks, with a profit-sharing system. This paper aims to examine theproblematic raw deal in mudharabah in Islamic banking. These problems willhave an impact on the lives of customers, where customers will feel aggrievedover contract made unilaterally. At first these customers want to get capital fortheir business because of the content of the burdensome contracts, selection of customers simply leave or not so do the financing by banks. If the customeraccepts the contract of cooperation, we can be sure the customer is running witha full big responsibility. In addition, the ratio of part of the customer will beless commensurate with the contribution of cooperation that customers provide.